Measuring Fear and Greed Index in Stock Market: Evidence from the Tehran Stock Exchange - Mojtaba Rostami Noroozabad; Ali Golbabaei Pasandi; Milad Shahrazi; Somayeh Esfandyari (تحقیقات مالی)
ObjectiveAccording to the hypothesis of behavioral finance, the main part of the ups and downs in the stock market can be the result of fear and greed. The Fear & Greed Index is a way to gauge stock market movements and determine if stocks are fairly priced. The theory is based on the logic that excessive fear tends to drive down share prices, and too much greed tends to have the opposite effect. The objective of this paper is to represent the fear and greed behavioral index daily in the Tehran Stock Exchange. MethodsThe sample for this research comprises all companies listed on the Tehran Stock Exchange from 2009/12/09 to 2023/08/22. The fluctuation in the number of accepted companies on the Tehran Stock Exchange is attributed to factors such as initial public offerings, the transfer of stocks between over-the-counter and the stock market, the delisting of symbols, and the cessation of trading for certain symbols. To apply the Fear and Greed Index in the Tehran Stock Exchange, we adapted CNN's Fear and Greed Index, making some modifications. Specifically, we retained seven variables while removing the Junk bond demand variable due to the absence of credit ratings for the debt securities traded on the Tehran Stock Exchange. Therefore, the represented index is based on the six variables, including stock market momentum, stock price strength, stock price breadth, put and call options, market volatility, and safe haven demand which shows the sentiments of the market in five scales, including excessive fear, fear, neutral, greed, and excessive greed. It should be noted that due to the diverse characteristics of the significant variables used in calculating the Fear and Greed Index and the need to consolidate all six variables into a single index, each variable is normalized using a standard method. ResultsThis study classifies the overall behavior of investors in the Tehran Stock Exchange into five sentiment spectrums: excessive fear, fear, neutral, greed, and excessive greed. The research findings reveal that during the years 2009, 2010, 2011, 2014 to 2016, and 2018 to 2023 (spanning from 2009/12/09 to 2023/08/22), the stock market exhibited higher levels of fear. Conversely, in 2012 and 2017, the Tehran Stock Exchange demonstrated a neutral sentiment on most trading days. Additionally, in 2013, the Tehran Stock Exchange displayed a greedy sentiment on the majority of its trading days. ConclusionIn total, from December 9, 2009, to August 22, 2023, out of 3299 working days, the Tehran Stock Market encountered excessive fear on 204 days, fear on 1604 days, neutrality on 878 days, greed on 565 days, and excessive greed on 48 days.